Same same but different? Integration of collective orientation(s) and their relationship with performance - Agethen, Katharina; Iseke, Anja
Organizational and research interest in collective orientation, an individual’s orientation towards groups, has been growing over the past decades. Yet, collective orientation remains a blurry concept. Integrating latent semantic analysis and meta-analyses, we systematize and compare conceptualizations and measures and thereby evaluate its importance for predicting individual and team performance.